Historic territorial estructuring road. The case of the route of the Cíbola, in the colonial period - Gómez-Molina, Pedro (2018)
The Route of the Cibola arose from a series of expeditions undertaken beginning in the 16th Century – taking advantage of old roads and prehispanic trails – that allowed the incursion and expansion into the northwestern region of New Spain. The route was studied by, inter alia, Carl Sauer, who brought  it international recognition. Our purpose here is to analyze this route cartographically and examine its territorial implications, which entails analysis of the geographical changes provoked concomitantly with the advance of the Colonial boundary. Th complementary, it analyzes the geographical changes that they provoked with de Colonial boundary advance. Notably, the old roads of the path was one of the factors facilitating the territorial expansion of New Mexico in the Mexican Northwest. For this study, we utilize primary document sources and process them through geographic information systems with a historical orientation (H-GIS).